2010
DOI: 10.1121/1.3488794
|View full text |Cite
|
Sign up to set email alerts
|

Spanish listeners’ perception of American and Southern British English vowels

Abstract: L2 studies demonstrate that learners differ in their speech perception patterns. Recent explanations attribute this variation to the different initial stages with which learners start their L2 development. Spanish listeners' categorization of Standard Southern British English and American English vowels is compared. The results show that, on the basis of steady-state F1 and F2 values, listeners classify the vowels of these two English varieties differently. This finding suggests that the dialect to which learn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
53
5
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(65 citation statements)
references
References 16 publications
6
53
5
1
Order By: Relevance
“…This proposal underlies recent cross-linguistic studies which examine the specific ways in which monolingual listeners map the sounds of a foreign language onto their native sound categories, e.g. Russian listeners of American English (AE) vowels (Gilichinkskaya and Strange, 2010), Peruvian Spanish (PS) listeners of AE and SSBE vowels (Escudero and Chládková, 2010), and PS listeners of Dutch vowels (Escudero and Williams, 2011). The present study contributes to the L2 initial state literature by comparing monolingual PS listeners' perception of the /e/-/ae/ contrast as produced in Canadian English (CE) and Canadian French (CF).…”
Section: Introductionmentioning
confidence: 96%
“…This proposal underlies recent cross-linguistic studies which examine the specific ways in which monolingual listeners map the sounds of a foreign language onto their native sound categories, e.g. Russian listeners of American English (AE) vowels (Gilichinkskaya and Strange, 2010), Peruvian Spanish (PS) listeners of AE and SSBE vowels (Escudero and Chládková, 2010), and PS listeners of Dutch vowels (Escudero and Williams, 2011). The present study contributes to the L2 initial state literature by comparing monolingual PS listeners' perception of the /e/-/ae/ contrast as produced in Canadian English (CE) and Canadian French (CF).…”
Section: Introductionmentioning
confidence: 96%
“…Experimental research has indeed demonstrated that cross-language assimilation patterns can be a useful predictor of second-language perception (e.g., Guion et al, 2000;Mayr and Escudero, 2010). Hence, several recent studies have investigated naive listeners' perception of non-native vowels in order to predict the initial stage of L2 development (Gilichinskaya and Strange, 2010;Escudero and Chládková, 2010;Escudero and Williams, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…That is, a learner's L2 targets may deviate further from her L1 targets as a function of L2 experience. In order to avoid such possible effects of perceptual learning, the perceived similarity between L1 and L2 vowels from a non-native identification task may be better predictive of initial L2 perceptual problems if undertaken by naïve listeners rather than L2 learners (e.g., Gilichinskaya and Strange, 2010;Escudero and Chládková, 2010). Escudero and Wanrooij (2010) have shown that specific perceptual problems persist for learners of Dutch with various L1 Spanish backgrounds.…”
Section: Introductionmentioning
confidence: 99%
“…Gilichinskaya and Strange, 2010) or synthetic stimuli (cf. Escudero and Chládková, 2010). A single speaker's vowels may reflect idiosyncratic speech production rather than typical productions of the language at hand, which may affect the extension of the results to a population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation